![image](https://tex.z-dn.net/?f=1.+%D0%B0%29+7%5Ex%3D%5Cfrac1%7B343%7D%5C%5C7%5Ex%3D%5Cfrac1%7B7%5E3%7D%5C%5C7%5Ex%3D7%5E%7B-3%7D%5C%5Cx%3D-3%5C%5Cb%29%5C%3B2%5E%7Bx%2B1%7D%3D4%5C%5C2%5E%7Bx%2B1%7D%3D2%5E2%5C%5Cx%2B1%3D2%5C%5Cx%3D1%5C%5C%5C%5C2.%5C%3B7%5E%7B2x-9%7D%3E7%5E%7B3x-6%7D%5C%5C2x-9%3E3x-6%5C%5C2x-3x%3E-6%2B9%5C%5C-x%3E3%5C%5Cx%3C-3%5C%5Cb%29%5C%3B%5Cleft%28%5Cfrac23%5Cright%29%5E%7B3x%2B6%7D%3E%5Cfrac49%5C%5C%5Cleft%28%5Cfrac23%5Cright%29%5E%7B3x%2B6%7D%3E%5Cleft%28%5Cfrac23%5Cright%29%5E2%5C%5C3x%2B6%3C2%5C%5C3x%3C-4%5C%5Cx%3C-%5Cfrac43)
7^{3x-6}\\2x-9>3x-6\\2x-3x>-6+9\\-x>3\\x<-3\\b)\;\left(\frac23\right)^{3x+6}>\frac49\\\left(\frac23\right)^{3x+6}>\left(\frac23\right)^2\\3x+6<2\\3x<-4\\x<-\frac43" alt="1. а) 7^x=\frac1{343}\\7^x=\frac1{7^3}\\7^x=7^{-3}\\x=-3\\b)\;2^{x+1}=4\\2^{x+1}=2^2\\x+1=2\\x=1\\\\2.\;7^{2x-9}>7^{3x-6}\\2x-9>3x-6\\2x-3x>-6+9\\-x>3\\x<-3\\b)\;\left(\frac23\right)^{3x+6}>\frac49\\\left(\frac23\right)^{3x+6}>\left(\frac23\right)^2\\3x+6<2\\3x<-4\\x<-\frac43" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=3.%5C%3B2%5Ccdot4%5Ex-5%5Ccdot2%5Ex%2B2%3D0%5C%5C2%5Ccdot%282%5E2%29%5Ex-5%5Ccdot2%5Ex%2B2%3D0%5C%5C2%5Ccdot2%5E%7B2x%7D-5%5Ccdot2%5Ex%2B2%3D0%5C%5C2%5Ex%3Dt%2C%5C%3B2%5E%7B2x%7D%3Dt%5E2%2C%5C%3Bt%3E0%5C%5C2t%5E2-5t%2B2%3D0%5C%5CD%3D25-4%5Ccdot2%5Ccdot2%3D25-16%3D9%5C%5Ct_1%3D2%2C%5C%3Bt_2%3D%5Cfrac14%5C%5C2%5Ex%3D2%5CRightarrow+x_1%3D1%5C%5C2%5Ex%3D%5Cfrac14%3D%5Cfrac1%7B2%5E2%7D%3D2%5E%7B-2%7D%5CRightarrow+x_2%3D-2%5C%5C%5C%5C4.%5C%3Ba%29%5C%3B%5Clog_215-%5Clog_230%3D%5Clog_2%5Cfrac%7B15%7D%7B30%7D%3D%5Clog_2%5Cfrac12%3D%5Clog_22%5E%7B-1%7D%3D-1%5C%5Cb%29%5C%3B3%5E%7B1%2B%5Clog_38%7D%7D%3D3%5Ccdot3%5E%7B%5Clog_38%7D%3D3%5Ccdot8%3D24)
0\\2t^2-5t+2=0\\D=25-4\cdot2\cdot2=25-16=9\\t_1=2,\;t_2=\frac14\\2^x=2\Rightarrow x_1=1\\2^x=\frac14=\frac1{2^2}=2^{-2}\Rightarrow x_2=-2\\\\4.\;a)\;\log_215-\log_230=\log_2\frac{15}{30}=\log_2\frac12=\log_22^{-1}=-1\\b)\;3^{1+\log_38}}=3\cdot3^{\log_38}=3\cdot8=24" alt="3.\;2\cdot4^x-5\cdot2^x+2=0\\2\cdot(2^2)^x-5\cdot2^x+2=0\\2\cdot2^{2x}-5\cdot2^x+2=0\\2^x=t,\;2^{2x}=t^2,\;t>0\\2t^2-5t+2=0\\D=25-4\cdot2\cdot2=25-16=9\\t_1=2,\;t_2=\frac14\\2^x=2\Rightarrow x_1=1\\2^x=\frac14=\frac1{2^2}=2^{-2}\Rightarrow x_2=-2\\\\4.\;a)\;\log_215-\log_230=\log_2\frac{15}{30}=\log_2\frac12=\log_22^{-1}=-1\\b)\;3^{1+\log_38}}=3\cdot3^{\log_38}=3\cdot8=24" align="absmiddle" class="latex-formula">